Small cell lung cancer transformation during antitumor therapies: A systematic review - Chai Xing (De Gruyter, 2021)
Lung cancer is the most common cause of cancer-related death. Non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) are the two major histological categories of lung cancers. Drug resistance is a great challenge for cancer treatment, and histological transformation from NSCLC to SCLC is one of the mechanisms underlying drug resistance in NSCLC patients. SCLC-transformed patients show combined characteristics of NSCLC and SCLC; however, they lack timely diagnoses and effective treatment strategies. Thus, we reviewed the clinical characteristics of SCLC transformation patients with a literature search to enhance clinical consciousness, diagnosis, and personalized treatment for patients with it.